Initial Immunopathogenesis of Multiple Sclerosis: Innate Immune Response - Norma Y. Hernández-Pedro; Guillermo Espinosa-Ramirez; Verónica Pérez de la Cruz; Benjamín Pineda; Julio Sotelo (Clinical and Developmental Immunology)
Multiple sclerosis (MS) is an inflammatory, demyelinating, and neurodegenerative disease of the central nervous system. The hallmark to MS is the demyelinated plaque, which consists of a well-demarcated hypocellular area characterized by the loss of myelin, the formation of astrocytic scars, and the mononuclear cell infiltrates concentrated in perivascular spaces composed of T cells, B lymphocytes, plasma cells, and macrophages. Activation of resident cells initiates an inflammatory cascade, leading to tissue destruction, demyelination, and neurological deficit. The immunological phenomena that lead to the activation of autoreactive T cells to myelin sheath components are the result of multiple and complex interactions between environment and genetic background conferring individual susceptibility. Within the CNS, an increase of TLR expression during MS is observed, even in the absence of any apparent microbial involvement. In the present review, we focus on the role of the innate immune system, the first line of defense of the organism, as promoter and mediator of cross reactions that generate molecular mimicry triggering the inflammatory response through an adaptive cytotoxic response in MS.